A política curricular do estado do Pará: impactos na formação dos sujeitos, das sujeitas na educação do campo no município de Tomé-Açu - RIBEIRO, João Vitor de Jesus (2025)
This study presents the theme of curricular policy as a power relation within the context of Rural Education in the municipality of Tomé-Açu. The objective is to reflect on the curricular policy of the state of Pará as an instrument of hegemony and its impacts on rural education and the formation of rural subjects. Using theoretical references such as Michael Apple, Tomaz Tadeu da Silva, and Miguel Arroyo, the study adopts a qualitative approach and documentary analysis (Cellard, 2008; Phillip, 1974), as I selected the Curricular Document of the State of Pará (DCEPará) as the research field. The results revealed that the curricular policy of the state of Pará is standardized and serves hegemonic interests. Its impact on rural education is felt in the dismantling of Rural Education, as the official curriculum begins to dictate standardized knowledge, stripping away freedom and critical thinking. This disregards local cultural identities, forming subjects displaced by globalization and adapted to the demands of capital. I conclude that this study contributes to a deeper understanding of the political and economic forces influencing curricular policies, providing support to strengthen resistance movements that fight for rural education with social quality, recognizing local identities and the real needs of rural subjects.